Supplementation of coated sodium butyrate relieved weaning stress and reshaped microbial flora in weaned lambs - Zhao, Fangfang; He, Wenhao; Wu, Tianyou; Elmhadi, Mawada; Jiang, Ning; Zhang, Aizhong; Guan, Pengyu (Frontiers in Veterinary Science, 2024)
Weaning is an important period in the growth and development of lambs, thus, effectively reducing the occurrence of weaning stress is critical for maintaining lamb production. Coated sodium butyrate has been reported to have the effect of resisting inflammation, promoting intestinal health and homeostasis. However, the application and potential mechanism of coated sodium butyrate in alleviating weaning stress in lambs are still unclear. To evaluate the effects of coated sodium butyrate on the growth performance, antioxidant capacity, and gut microbiota of weaned lambs, ten weaned lambs of 21 day old were randomly divided into two treatments: CON group (basal diet) and NaB group (basal diet + 3 g/kg coated sodium butyrate), the trial last for 21 days. The experimental results showed that compared with the control group, coated sodium butyrate supplementation in the diet significantly increased the average daily weight gain and daily feed intake of lambs (P<0.05). In addition, compared with the CON group, the addition of coated sodium butyrate also significantly decreased the serum MDA level of lambs (P<0.05). Notably, the addition of coated sodium butyrate did not have a significant effect on the cecal microbiota, while increased the diversity of colonic microbiota and promoted the abundance of Lachnospiraceae, Verrucomimicrobia, Akkermansia, Roseburia, and Sinobacteraceae, which are associated with the nutrient absorption of lambs (P<0.05).These results indicate that coated sodium butyrate supplementation in the diet could promote the growth and antioxidant capacity of weaned lambs, and alleviate weaning stress.